2004
DOI: 10.1093/ageing/afh063
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of implementing a care pathway for femoral neck fracture in older people: a prospective controlled before and after study

Abstract: This care pathway was associated with longer hospital stay and improved clinical outcomes. Care pathways for hip fracture patients can be a useful tool for raising care standards but may require additional resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
114
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 11 publications
1
114
0
2
Order By: Relevance
“…Published prospective intervention studies are small and therefore underpowered to detect differences in mortality. 19,20 The purpose of the present study was to determine if our improvement intervention achieved the intended reduction in time to surgery and if a reduction in time to surgery improved mortality and length of stay (LOS). We believe that this work is unique in that it is, to our knowledge, the first adequately powered intervention study that examines the association between timely hip fracture surgery and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Published prospective intervention studies are small and therefore underpowered to detect differences in mortality. 19,20 The purpose of the present study was to determine if our improvement intervention achieved the intended reduction in time to surgery and if a reduction in time to surgery improved mortality and length of stay (LOS). We believe that this work is unique in that it is, to our knowledge, the first adequately powered intervention study that examines the association between timely hip fracture surgery and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Leigheb et al showed similar reductions in the hospital length of stay in eight out of 12 studies [6]. Three studies reported a longer hospital stay [14][15][16] and one did not find any difference after implementing a clinical pathway [17].…”
Section: Discussionmentioning
confidence: 99%
“…This shifts care from a condition focus to meeting individual needs. However, the medical model of care dominates recovery processes and is seen in clinical pathways (Choong et al, 2000;Olsson et al, 2006;Roberts et al, 2004). Advocates of clinical pathways argue that this process benefits both patient and organisation by reducing in-hospital days and improving outcomes.…”
Section: Discussionmentioning
confidence: 99%